Futile Pursuits of Metonymic Targets in Political and Legal Contexts - Twardzisz, Piotr (Linguistik Online, 2014)
This article explores problematic aspects of metonymic target identification in specialist language. Searching for and establishing metonymic targets has been the goal of numerous studies pursued in cognitive linguistics. Not infrequently, one may get the impression that the deliberate refinement of the metonymic reference point, geared to bring in more semantic precision, leads to confusing and inconsistent results. In this article, the focus will be on unveiling such confusing and inconsistent cases of metonymic target identification in political and legal contexts. For this purpose, three case studies will be analysed. In one of these, it will be shown how the interlocutors deliberately play with reference points/targets for rhetorical purposes. In another case, an example of target identification will be reviewed in which the linguist/researcher arbitrarily proposes metonymic targets. As a third example, a case of metonymic target identification in a legal document will be reviewed. A closer look at the co-referring entities, the major players in this document, reveals an error made by the drafters. This case is illustrative of a certain erroneousness underlying the assumption of straightforward and automatic target identification.